ESTIMATING NUMBER DENSITY NV – A COMPARISON OF AN IMPROVED SALTYKOV ESTIMATOR AND THE DISECTOR METHOD - Davtian, Ashot; Hahn, Ute; Ohser, Joachim; Stoyan, Dietrich (Image Analysis and Stereology, 2011)
Two methods for the estimation of number per unit volume NV of spherical particles are discussed: the (physical) disector (Sterio, 1984) and Saltykov's estimator (Saltykov, 1950; Fullman, 1953). A modification of Saltykov's estimator is proposed which reduces the variance. Formulae for bias and variance are given for both disector and improved Saltykov estimator for the case of randomly positioned particles. They enable the comparison of the two estimators with respect to their precision in terms of mean squared error.